2016
DOI: 10.14742/ajet.2164
|View full text |Cite
|
Sign up to set email alerts
|

Learning outcome, presence and satisfaction from a science activity in Second Life

Abstract: Although problem-based learning (PBL) has many advantages, it often fails to connect to the real world outside the classroom. The integration with the laboratory setting and the use of information and communication technologies (ICTs) have been proposed to address this deficiency. Multi-user virtual environments (MUVEs) like Second Life (SL) are 3D collaborative virtual environments that could act as complementary or alternative worlds for the implementation of laboratory PBL activities offering low-cost, safe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
36
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 52 publications
(98 reference statements)
2
36
0
1
Order By: Relevance
“…Alvarez and Cuesta (2012) suggest that an adequate analysis and implementation of these interactional modes should aim at providing students with the opportunity to customise their learning experiences according to their needs, styles, skills, demographics, previous learning history with online formats, and beliefs. Consequently, interaction outcomes should favour satisfaction, participation, communication, exploration, and self-regulation processes (Cuesta Medina, 2010;Palmer & Holt, 2014;Rourke, Anderson, Garrison, & Archer, 1999;Vrellis, Avouris, & Mikropoulos, 2016;Wagner, 1997).…”
Section: The Origins Of Blmentioning
confidence: 99%
“…Alvarez and Cuesta (2012) suggest that an adequate analysis and implementation of these interactional modes should aim at providing students with the opportunity to customise their learning experiences according to their needs, styles, skills, demographics, previous learning history with online formats, and beliefs. Consequently, interaction outcomes should favour satisfaction, participation, communication, exploration, and self-regulation processes (Cuesta Medina, 2010;Palmer & Holt, 2014;Rourke, Anderson, Garrison, & Archer, 1999;Vrellis, Avouris, & Mikropoulos, 2016;Wagner, 1997).…”
Section: The Origins Of Blmentioning
confidence: 99%
“…According to the results, both the virtual world and real world groups' satisfaction and presence scores were high. There was also a positive correlation between presence and satisfaction (Vrellis, Avouris, & Mikropoulos, 2016).…”
Section: Social Presence and Motivation In Sl Learning Environmentsmentioning
confidence: 80%
“…Thus, the younger participants could easily feel as if they were in the environment and at the time, even considered others as real persons. One study [8] found that the place presence scores were moderate although the participants had prior virtual world experiences. Hence it is unsurprising for the senior participants of this study to have lower place presence scores than did the young participants.…”
Section: B Discussionmentioning
confidence: 99%
“…To counter some drawbacks a new technology called three-dimensional (3-D) virtual world has been progressively applied in online collaborative learning because the method holds various potentials in supporting interaction and communication among students [5]. The technology is also capable of generating many forms of presence, such as place presence, social presence, and co-presence [6]- [8].…”
Section: Introductionmentioning
confidence: 99%